ANALISIS DAYA AKTIF, KONSUMSI ENERGI, DAN BIAYA LISTRIK MOTOR GM-315 PADA COOLING TOWER DI PT. POLYCHEM INDONESIA TBK - Anggie Maulia; Bagus Dwicahyono (Pusat Penelitian dan Pengabdian Masyarakat, 2026)
Polychem Indonesia Tbk is a chemical industry company that requires a large amount of electrical energy to support its production operations, one of which is in the cooling tower system. This study analyzes the GM-315 three-phase induction motor used to drive the cooling tower pump to calculate the active power, energy consumption, and electricity costs incurred. This research uses a descriptive quantitative approach with measurements of current and voltage from the actual GM-315 motor obtained from the soft starter. The measurement results show that the GM-315 motor has active power ranging from 163.02 kW to 176.82 kW, with energy consumption reaching 4,243.68 kWh per day under the highest load condition. The electricity cost calculations show that the highest cost occurred in the GM-315 A motor, amounting to Rp 4,229,845.60 per day. This study aims to provide a clearer picture of energy consumption and costs that can be used to improve energy efficiency and electricity cost management at PT. Polychem Indonesia Tbk.